The Possible Non-Mutational Causes of FVIII Deficiency: Non-Coding RNAs and Acquired Hemophilia A - Zimta, Alina-Andreea; Hotea, Ionut; Brinza, Melen; Blag, Cristina; Iluta, Sabina; Constantinescu, Catalin; Bashimov, Atamyrat; Marchis-Hund, Elisabeth-Antonia; Coudsy, Alexandra; Muller-Mohnssen, Laetitia; Dirzu, Noemi; Gulei, Diana; et al. (Frontiers in Medicine, 2021)
Hemophilia type A (HA) is the most common type of blood coagulation disorder. While the vast majority of cases are inherited and caused by mutations in the F8 gene, recent data raises new questions regarding the non-heritability of this disease, as well as how other molecular mechanisms might lead to development of HA or increase the severity of the disease. Some data suggests that miRNAs may affect severity of HA, but for some patient’s, miRNA-based interference might cause HA, in the absence of an F8 mutation. A mechanism in HA installation that could be identified in the future is the epigenetic silencing of the F8 gene that might be only temporarily, and it is also worth investigating. Finally, acquired HA is becoming increasingly reported and as more cases are identified, the description of the disease might be challenges as cases without FVIII autoantibodies might be identified.